Economic Devocalization and Survival in Toni Morrison’s Home (2012) and God Help the Child (2015) - Eyang, Anthony Ebebe; Okpene, Dominic Enamhe (ELT Worldwide: Journal of English Language Teaching, 2021)
The dimensions of strategic and systematic silencing in America have ramifications for the economic survival of African Americans. The motif of devocalization has been creatively engaged in Toni Morrison’s Home and God Help the Child (2015). Through experimentation with language, Morrison has mobilized her linguistic genius towards the exploration of the themes of mobility, devocalization, commodification, and convolution of other themes. Through this, Morrison once again establishes the intricate connection between her language and her artistic vision, vis-à-vis her commitment to the African American cause. A psychoanalytic evaluation of her themes of strategic economic silencing, poverty, and systematic devocalization, validates Freud’s pleasure vs reality principle, unearthing her characters’ emotional imbalances and how they channel the untapped desires for pleasure towards a productive end in the face of their harrowing realities. New historicism helps the paper to situate the collective complex of the African American community within the different historical periods, espousing the different discourses and how they inform and are informed by the emotional climate of the times.